Behavior of sunflower cultivars at difffrent planting dates in the uplands of Santa Catarina - Sangoi, Luis; Kruse, Nelson D. (Pesquisa Agropecuaria Brasileira, 1993)
This work was carried out with the purpose of evaluating the effects of planting dates on grain yield, oil percentage and oil yield of sunflower (Helianthus annuus) cultivars in the uplands of Santa Catarina state, Brazil. The experiment was carried out during 1987/88 and 1988/89 growing seasons under two soil conditions. In 1987/88 the trial was installed without previous pH correction. The planting dates assayed in this year were September 19, October 20, November 11 and December 9. In 1988/89 lime was applied three months before the beginning of the work and the planting dates tested were September 16, October 14, November 17 and December 14. The cultivars used were Contissol 711 and Dk 180. Under natural soil pH conditions, gram yields were low and the effect of planting date on grain and oil yield was not pronounced. In this case, Contissol 711 showed higher grain and oil yield than Dk 180. With file previous lime application to the soil, sunflower cultivars showed the highest grain and oil yields when sowing was done at September.